Vertebral osteomyelitis in an adolescent girl - Salloum, Shafee (SAGE Open Med Case Rep, 2020)
We present a case of a 13-year-old girl with vertebral osteomyelitis. She had been experiencing lower back pain for 5 weeks, initially thought to be due to muscular causes. The blood culture showed no bacterial growth, and she was treated empirically only with antibiotics. She responded well to treatment and required no surgical intervention. Vertebral osteomyelitis should be in the differential diagnosis in an adolescent who complains of worsening lower back pain. Early diagnosis and treatment are essential in avoiding complications.